Properties of electrical insulator ceramic with kaolinite from Tinkham village, Thulakhom district, Vientiane province - Souksomvang, Phouvanh; Bounyavong, Sengthong; Vorlachak, Niphon; Padtha, Phayvanh; Tonpheng, Bounphan (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The purpose of this study was to find out the physical properties of insulator electric ceramics, which used kaolinite from Thinkham village, Thulakhom district, Vientiane province, mixed with quartz and feldspar. The quality of raw materials was improved by the ball mill, which the size was about 45-75 µm. The raw material's chemical composition was studied by XRF before mixing and preparing samples. The ceramic sample consisted of 5 components (25 samples) by decreasing the amount of kaolinite and increasing the feldspar, then annealling at 950, 1000, 1050, 1100 and 1150oC respectively. The results of the chemical composition indicate that the main chemical in kaolinite raw materials from Thinkham village are SiO2 (63.30%) and Al2O3 (24.42%), as well as Fe2O3 (8.31%) and a few number of other elements, the quartz raw materials show high pure with consist of SiO2 (97.14%), and the felspar raw materials are contain SiO2 (70.85%), Al2O3 (13.72%) and Fe2O3 (1.99%). The results of physical properties investigation show as the water absorption, the volume of open pores, and the apperent pores are decrease with decreasing amount of kaolinite and increase the combustion temperature, in another results the bulk density and the bending strength has increased. In addition, the electric specific resistance of the samples also increased.